Sofroniusz, mnich palestyński, wobec monoenergizmu. Napięcie między precyzją a dwuznacznością - Kashchuk, Oleksandr (Vox Patrum, 2018)
The scholars who examined the Miaenergist confrontation focused their attention on the different aspects of the controversy. The purpose of the article is to understand whether the sociocultural matter could also be covered in confrontation between Sophronius of Jerusalem and Sergius of Constantinople. Sophronius’ views were formed in the circle of the Palestinian monasticism, which was strongly loyal to the verbal confession of two-nature Chalcedonian Christology. Accordingly, he expressed his protest against the statement on one operation in Christ. In response, Sergius of Constantinople developed his tactics in order to defend the stance of the Church and Court of Constantinople. As a result, a significant tension between the both Patriarchs arose.